Analisis Usahatani Kale Curly di XZY Organik Kecamatan Parongpong Kabupaten Bandung Barat - Pardian, Pandi; Heryanto, Mahra Arari (Universitas Galuh, 2024)
As one of the agribusiness sub-systems, farming activities carried out by individuals, groups, and industries carry it out. Still, it becomes fascinating if what is cultivated is organic vegetable commodities and becomes a business with limited land, even using only 22 m2 of land in the form of 4 raised-bed gardenings. This research tries to conduct a farming analysis of one commodity from several cultivated commodities. This research uses quantitative description methods through the collection process, interpretation, and analysis to explain actual conditions. The research results show that kale curly farming is worth pursuing with a profit of 88.42% and an R/C ratio of 8.64 or greater than one by maintaining the existing market niche and developing the organic product market.